Spontaneous Electric Polarization in Graphene Polytypes - Atri, Simon Salleh; Cao, Wei; Alon, Bar; Roy, Nirmal; Stern, Maayan Vizner; Falko, Vladimir; Goldstein, Moshe; Kronik, Leeor; Urbakh, Michael; Hod, Oded; Ben Shalom, Moshe (Advanced Physics Research, 2024)
Spontaneous electric polarization is recently observed in multilayered van der Waals stacked materials, arising from a symmetry breaking in a unit cell with two or more constituent species, or non‐centrosymmetric intra‐layer atom displacement in single‐atom‐species materials. Here, it is shown that even elemental crystals, consisting of one type of atom and composed of non‐polar and centrosymmetric layers, exhibit electric polarization if arranged in an appropriate three‐dimensional  architecture. This concept is demonstrated here for mixed‐stacking tetra‐layer polytypes of non‐polar graphene sheets. Surprisingly, it is find that the room temperature out‐of‐plane electric polarization increases with external electrostatic hole doping, rather than decreases with it owing to screening. Using first‐principles calculations, as well as a self‐consistent tight‐binding model, the emergence of polarization is explain in terms of inter‐layer charge rearrangement and the doping dependence in terms of gating‐induced inter‐layer charge transfer. This newly discovered intrinsic polarization may therefore offer new venues for designing the electronic response of graphene‐based polytypes to external fields. Internal electric polarization in a periodic crystal requires a non‐centrosymmetric unit cell. Usually, the different atomic species in each cell break the symmetry and polarize the inter‐atomic bonds, thus hiding the purely geometrical contribution of the atomic positions. The current report reveals a room‐temperature polarization in elemental layered crystals of carbon atoms only. It explores fascinating electronic distributions in such metastable van der Waals polytypes of various structural configurations and symmetries.